Isolation and Chacterisation of Cysteine Selenotrisulfide - Pandian, K.; Sriman Narayanan, S. (Asian Journal of Chemistry, 2010)
Cysterine selenotrisulfide formed by the reaction of selenite with L-cysteine in acid solution has been isolated and characterized by thin layer chromatographic experiments, FAB-MS spectra and IR spectra. Thermal experiments revealed that the compound is stable up to 190ºC. Abrasive stripping voltammetric results have shown that this compound undergoes electrochemical reduction in two steps.